The Effectiveness of KAHOOT In Teaching Remote Listening Skill Among Students of Ruhama Islamic Intermediate School Tangerang - Muslimin, Muhamad Ihwanul; Hamdani, Imron (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah, 2024)
The researcher chose this topic based on the presence spread of the Corona virus Covid-19, which causes great changes in people's lives, including changes in the field of education. The aim of this research is to reveal the results of the tests that use the Kahoot remote method for the students and do not use it, and to reveal the effectiveness of the Kahoot method in teaching he remote listening skill. This research followed a semi-experimental study based on the quantitative approach, and its design consisted of the experimental group and the control group. The researcher used data collection methods, which are direct observation, personal interview, tests and questionnaires. After the researcher analyzed the data, reached the mean of the two tests, the pre-test and the post-test. Based on the average results of the experimental group at a value of 28.75 and the average results of the control group at a value of 16.75, it indicates that the average results of the experimental group are greater than the average results of the control group. And I came to the analysis of the data using the "t" test rule. The result of the arithmetic t0 (t0) is 2.79, so the table is at the level of significance of 5% on the value of 1,686 and the level of significance of 1% on the value of 2,429, and this indicated that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) accepted. This means that the use of the Kahoot method in teaching the remote listening skill of the pupils of this school is statistically significant.